THE INFLUENCE OF BUDGETING PARTICIPATION, ORGANIZATIONAL CULTURE AND LOCUS OF CONTROL ON PERFORMANCE ACCOUNTABILITY: A CASE STUDY IN MALUKU PROVINCE GOVERNMENT - Elna Marsye Pattinaja; Tirza Oktovianti Lenggono; Junadya Swinita Wattimury; Regina Apituley (Jurnal Ekonomi, 2023)
This study aims to empirically examine the effect of participatory budgeting, organizational culture and locus of control on performance accountability of government agencies. The method used in this study uses multiple linear regression analysis. The sample in this study were structural officials of the Maluku Province regional apparatus organization (OPD). The results of the study show that based on the output results of multiple linear regression tests, budgeting participation and organizational culture have a positive value, but the locus of control variable has a negative value, which means that even though the locus of control has increased, accountability for the performance of government agencies has remained stable or has not enhancement. However, the results of the t test prove that the variable budgeting participation, organizational culture and locus of control have a significant effect on the performance accountability of government agencies.